Vogt-Koyanagi-Harada Syndrome: A case report - Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The Vogt-Koyanagl-Harada Syndrome is characterized by bilateral panuveitis and exudative retinal detachments, in association with cutaneous and neurosensory manifestations. This syndrome is seen most commonly in darker pigmented races, such as Orientals, Hispanics, American Indians, and blacks. It affects both sexes, although it appears to be a distinct female predominance. Most patients are between 20 to 50 years of age, but children and older adults also may be affected. A patient with some clinical symptoms of Vogt-Koyanagi-Harada (VKH) syndrome was reported. This patient had chronic bilateral iridocyclitis, posterior uveitis, exudative retinal detachment, cataracts related to cutaneous manifestations. This patient well responded on ophthalmologic manifestations by corticosteroid treatment but the other signs of VKH syndrome were still developing after 4 months period. The therapy for VKH syndrome was the high doses of systemic corticosterolds, and, with the severity of the anterior uveitis, topical corticosteroid was administrated frequently. A short-acting corticosteroid such as prednisone, in the range of 100-120 mg/day was given, based on the severity of the Inflammation. Some patients might require the addition of cytotoxic agents or cyclosporine.Key words : Vogt-Kayanagi-Harada syndrome - bilateral iridocyclitis - exudative retinal detachment - cutaneous manifestations.